St. Kitts and Nevis : Ninth and Final Review Under the Stand-By Arrangement, Request for Waiver of Nonobservance of Performance Criterion, and Proposal for Post-Program Monitoring. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Stand-By Arrangement (SBA): The 36-month SBA for SDR 52.51 million (590 percent of quota) was approved on July 27, 2011. The seventh and eighth reviews were completed on March 19, 2014, together with the 2014 Article IV consultation. The authorities plan to continue to treat the arrangement as precautionary, which they began at the last review, and have repaid early a portion of the Fund's outstanding credit (about 125 percent of quota). Context: Growth is expected to continue at a relatively rapid pace, following a stronger- than-expected recovery of nearly 4 percent in 2013, after a four-year contraction. This reflects rapid expansion in construction related to large Citizenship-by-Investment inflows, and a substantial increase in public sector investment, as well as support from the People Employment Program (PEP). The ECCB is investigating the reclassification of two public sector loans targeted for restructuring that may adversely impact banks' financial soundness indicators. Program performance: Substantial strides have been made under the government's home-grown economic program. Fiscal sustainability has improved, debt was substantially reduced and is on a downward path, the financial sector has remained stable, and key structural reforms have been implemented. The fiscal program is on track and all performance criteria were met with the exception of the continuous performance criterion on external arrears. The external arrears were minor and quickly repaid. Progress on the implementation of structural reforms is slow, with delay in one of the two benchmarks that were to be completed for this review, which is now a prior action. Review: The authorities continue to demonstrate their commitment to their home- grown program, and are on track to meet the 2014 fiscal targets. They also plan to press ahead with their structural reform agenda and complete reforms initiated under the program. With ongoing implementation of prudent fiscal management, the authorities are on track to reduce debt to 60 percent of GDP by 2020. In accordance with Fund policy, the Managing Director is recommending the initiation of Post-Program Monitoring (PPM).